DAMPAK KORUPSI DANA BANTUAN TERHADAP PERTUMBUHAN EKONOMI, STABILITAS FISKAL, DAN KETIMPANGAN DI INDONESIA - Alfian Khoiri Malau; Muhammad Dzikry Falah Erlangga; Nadira Aulia Zahra; Ahmad Wahyudi Zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Corruption in the funding of social assistance continues to be a serious issue because of its significant impact on Indonesia's economy. This study aims to analyze the effects of corrupt practices in aid funds on three main aspects of the national economy, namely economic growth, fiscal stability, and socio-economic inequality. The method used in this study is a descriptive qualitative approach, combining literature review and analysis of current cases. The results of the study show that corruption in aid funds not only causes losses to state finances but also has long-term effects that can hinder economic growth, disrupt fiscal balance, and widen social inequality, potentially reducing the rights of the poor as beneficiaries. It can be seen from the analysis of several cases, ranging from the misuse of Covid-19 aid funds, the Indonesia Smart program, disaster aid, to the public housing program, which show evidence of state losses reaching trillions of rupiah. Therefore, these findings emphasize that aid funds can have a significant and layered negative impact on the national economy. For this reason, comprehensive improvements are needed in managing aid funds by strengthening the oversight system, increasing transparency, utilizing advanced digital technology, and imposing strict sanctions on perpetrators of corruption to prevent them from committing it again.